Opening our eyes to a critical approach to medicine: The humanities in medical education. (1st February 2017) - Liao, Lester
Abstract: This paper examines a recent medical graduate's perspective on how undergraduate education tends to focus on imparting medical knowledge with little reference to the human aspects in clinical medicine. This is problematic because medicine is both about people and practiced by people. Students often have minimal exposure to the humanities prior to and in medical school and are frequently unaware of the societal trends that impact their view of medical practice. Familiarity with the humanities is a crucial means to understanding human nature, recognizing personal sociocultural biases, and practicing patient-centered medicine. This gap in knowledge may be due to the increase in medical information and optimistic ideologies related to medical progress. Philosophical paradigms and historical examples are considered to demonstrate the relevance of both fields in the humanities in understanding the role of moral human agents in applying medical knowledge. Educational changes in the humanities are proposed as a potential solution to our current deficits. Informal changes include mentorship relationships and shifting the general underpinning attitude in medical culture. Formal changes include specific courses teaching a critical approach to medicine. Changes in competency-based education and admissions are also suggested. These amendments are proposed to practice a fuller, truly human medicine.